(untitled) (Agricultural Engineering, 2017)
The paper presents analysis of the processes taking place in fuel systems which lead to damage of injection devices in farm machines. The most frequent reasons of failure of traditional injection systems and Common Rail high pressure systems which are caused inter alia by an improper quality of diesel oil were described and discussed. Microscopic tests of the surface of worn plungers of the plunger and barrel assemby of Motorpal injection pumps used in Zetor tractors were carried out. Types of damage to elements of the injection pump and electromagnetic injectors used in Common Rail systems CP4 type based on the tests on the group of 126 on-site repairs were assessed. Repairs were made in the repair centres in Podkarpackie Voivodeship and centres dealing with repair of injection systems. Metallographic tests were carried out in the Laboratory of Materials of Rzeszow University of Technology with the use of electrone scanning microscope Hitachi S-3400N.